Nomogram for predicting post-traumatic hydrocephalus after decompressive craniectomy for traumatic brain injury - Zhuo,Jianwei (2022)
SUMMARY OBJECTIVE: This study aimed to develop and validate a practical nomogram to predict the occurrence of post-traumatic hydrocephalus in patients who have undergone decompressive craniectomy for traumatic brain injury. METHODS: A total of 516 cases were enrolled and divided into the training (n=364) and validation (n=152) cohorts. Optimal predictors were selected through least absolute shrinkage and selection operator regression analysis of the training cohort then used to develop a nomogram. Receiver operating characteristic, calibration plot, and decision curve analysis, respectively, were used to evaluate the discrimination, fitting performance, and clinical utility of the resulting nomogram in the validation cohort. RESULTS: Preoperative subarachnoid hemorrhage Fisher grade, type of decompressive craniectomy, transcalvarial herniation volume, subdural hygroma, and functional outcome were all identified as predictors and included in the predicting model. The nomogram exhibited good discrimination in the validation cohort and had an area under the receiver operating characteristic curve of 0.80 (95%CI 0.72–0.88). The calibration plot demonstrated goodness-of-fit between the nomogram’s prediction and actual observation in the validation cohort. Finally, decision curve analysis indicated significant clinical adaptability. CONCLUSION: The present study developed and validated a model to predict post-traumatic hydrocephalus. The nomogram that had good discrimination, calibration, and clinical practicality can be useful for screening patients at a high risk of post-traumatic hydrocephalus. The nomogram can also be used in clinical practice to develop better therapeutic strategies.